1997
DOI: 10.1161/01.cir.95.8.2044
|View full text |Cite
|
Sign up to set email alerts
|

Improved Procedural Results of Coronary Angioplasty With Intravascular Ultrasound–Guided Balloon Sizing

Abstract: The demonstration by IVUS of atheromatous remodeling permits the safe use of balloons traditionally considered oversized, resulting in significantly improved luminal dimensions without increased rates of dissection or ischemic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
6

Year Published

1997
1997
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(47 citation statements)
references
References 30 publications
1
40
0
6
Order By: Relevance
“…Subsequent dilatation with these traditionally oversized balloons resulted in a significant increase in MLD (from 1.95Ϯ0.49 to 2.21Ϯ0.47 mm) without a corresponding increase in the incidence of angiographic dissection. 54 Measurement of coronary flow reserve using the Doppler guidewire represents another potential end point on which to base the decision of whether to provisionally stent a lesion after balloon angioplasty has been completed. 55 In a preliminary clinical trial, patients in whom normalization of coronary flow reserve did not occur immediately after angiographically successful balloon angioplasty demonstrated an increased risk for recurrent events and may represent a subgroup who would benefit from provisional stent placement.…”
Section: The "Aggressive" Approach To Angioplastymentioning
confidence: 99%
“…Subsequent dilatation with these traditionally oversized balloons resulted in a significant increase in MLD (from 1.95Ϯ0.49 to 2.21Ϯ0.47 mm) without a corresponding increase in the incidence of angiographic dissection. 54 Measurement of coronary flow reserve using the Doppler guidewire represents another potential end point on which to base the decision of whether to provisionally stent a lesion after balloon angioplasty has been completed. 55 In a preliminary clinical trial, patients in whom normalization of coronary flow reserve did not occur immediately after angiographically successful balloon angioplasty demonstrated an increased risk for recurrent events and may represent a subgroup who would benefit from provisional stent placement.…”
Section: The "Aggressive" Approach To Angioplastymentioning
confidence: 99%
“…[5][6][7] Prior studies have demonstrated that ICUS provides information not generated by angiography 8 -11 and that the use of sonographic measurements of vascular dimensions improves angiographic results. [12][13][14] The Strategy for ICUS-Guided PTCA and Stenting (SIPS) trial randomized consecutive patients to either a strategy of initial ICUS-guided treatment or use of angiographic guidance (Angio) alone. The primary end point of the study was 6-month angiographic minimal lumen diameter (MLD).…”
mentioning
confidence: 99%
“…The strategy of IVUS-guided PTCA, which was initially described in the Clinical Outcomes with Ultrasound Trial, 14 has shown favorable long-term clinical outcomes. 14,15 This strategy has matured into IVUS-guided provisional stenting by using IVUS criteria for stenting in addition to IVUS balloon sizing, 17,21,22 thus leading to better results than with angiography-guided provisional stenting. 19 In this context, the time was right for a randomized comparison of this IVUS-guided strategy with systematic stenting.…”
Section: Methodsmentioning
confidence: 99%
“…14,15,[17][18][19]21 IVUS criteria for crossover to stent (Ͻ30% residual stenosis or Ͻ6 mm 2 minimum L-CSA) were adapted from previous IVUS-guided PTCA studies, 17,19 except regarding non-flow-limiting dissection, because several trials have shown favorable clinical outcomes in these cases. 15,21,25 Crossover to stent was needed in 44% of patients; this rate is comparable to that observed in previous IVUS-guided PTCA studies, 17,19 but it is higher than the usual 30% reported in studies with angiographic guidance alone.…”
Section: Methodsmentioning
confidence: 99%